"nosotros ya decidimos": resistencia y territorialidad en la comunidad campesina e indígena san juan de cañaris - lambayeque frente al proyecto minero "cañariaco" - Aguilar Dueñas, Pável Francoise (2014)
This research focuses on studying the causes why the Peasant and lndigenous. Community San Juan of Cañaris in Lambayeque opposes "Cañariaco Project" of the Canadian mining company Candente Cooper Corp. This approach to political ecology of the transformations used territorial, which privileges the territorial approach to narrativas of local people from their own locus. This conflict also expresses so particularly sorne of the most significant features of the Peruvian extractivismo: tensions between the companies, the state and communities; the subject of consultation, environmental governance of the territories and the emergen ce of social and en vi ron mental movements are steadily • challenging the neoliberal model